2016
DOI: 10.1016/j.jalz.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Two novel loci, COBL and SLC10A2, for Alzheimer's disease in African Americans

Abstract: Introduction African Americans’ (AAs) late-onset Alzheimer’s disease (LOAD) genetic risk profile is incompletely understood. Including clinical covariates in genetic analyses using informed conditioning might improve study power. Methods We conducted a genome-wide association study (GWAS) in AAs employing informed conditioning in 1825 LOAD cases and 3784 cognitively normal controls. We derived a posterior liability conditioned on age, sex, diabetes status, current smoking status, educational attainment, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…Extensions of these findings and the contributions of additional loci have emerged from investigations of non-EA cohorts, African Americans (AAs) in particular (Reitz et al, 2013a; Mez et al, 2017). The risk of AD is greater in AAs than EAs, however, paradoxically, 𝜀4 has a weaker effect in AAs than EAs (Farrer et al, 1997; Reitz et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Extensions of these findings and the contributions of additional loci have emerged from investigations of non-EA cohorts, African Americans (AAs) in particular (Reitz et al, 2013a; Mez et al, 2017). The risk of AD is greater in AAs than EAs, however, paradoxically, 𝜀4 has a weaker effect in AAs than EAs (Farrer et al, 1997; Reitz et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Proposed environmental risk factors include a history of head trauma [2][3][4] and infection [5][6][7]. In recent years, large-scale genome-wide association studies (GWAS) and family-based studies have made considerable progress in defining the genetic component of AD risk, and >30 AD risk loci have been identified [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of the characteristic plaques and neurofibrillary tangles was reported not to differ between African Americans and Caucasians with AD [19][20][21], a more recent study described increased AD-associated neuropathology in African Americans [22]. Further, there are now four late-onset AD risk genes identified for African Americans from genome-wide association studies and one of those gene variants is found only in African Americans [23,24]. Such studies indicate the advantage of using different approaches to understanding what is likely to be a complex picture of AD-related ethnicity differences.…”
Section: Introductionmentioning
confidence: 99%